2015
DOI: 10.1007/s11606-015-3480-6
|View full text |Cite
|
Sign up to set email alerts
|

Low ALT Levels Independently Associated with 22-Year All-Cause Mortality Among Coronary Heart Disease Patients

Abstract: BACKGROUND: Low alanine aminotransferase (ALT) blood levels are known to be associated with frailty and increased risk of long-term mortality in certain populations. However, the contribution of this marker to longterm outcome has not been assessed in patients with chronic coronary heart disease. OBJECTIVE: The aim of the current study was to assess the association between low ALT values and long-term, 22.8-year, all-cause mortality in this population. PARTICIPANTS: We examined the association of low ALT (<17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
40
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 15 publications
4
40
1
Order By: Relevance
“…Previous longitudinal studies suggested that low ALT <13–19 IU/L levels increase frailty, disability and mortality . The present study also showed that similar cut‐off values of ALT <18.5 IU/L can predict the risk of low muscle strength in older patients with diabetes.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Previous longitudinal studies suggested that low ALT <13–19 IU/L levels increase frailty, disability and mortality . The present study also showed that similar cut‐off values of ALT <18.5 IU/L can predict the risk of low muscle strength in older patients with diabetes.…”
Section: Discussionsupporting
confidence: 79%
“…22 Low ALT level is also a negative factor that increases cardiovascular and all-cause mortality. 9,23 Based on these data, it seems that there is a "missing link" between low DBP and low ALT.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In this study, Peltz-Sinvani et al 1 assessed the association between low ALT (<17 IU/L) blood levels and long-term (22.8 years) all-cause mortality in patients with stable coronary heart disease. The authors used the Bezafibrate Infarction Prevention (BIP) registry population, which contains over 15,000 patients 40 to 74 years of age with stable coronary heart disease who have been followed continuously for over two decades.…”
mentioning
confidence: 99%